Subwavelength Grating Structures in Silicon-on-Insulator Waveguides. (13th July 2008) - Schmid, J. H.; Cheben, P.; Janz, S.; Lapointe, J.; Post, E.; Delâge, A.; Densmore, A.; Lamontagne, B.; Waldron, P.; Xu, D.-X.
Abstract : First implementations of subwavelength gratings (SWGs) in silicon-on-insulator (SOI) waveguides are discussed and demonstrated by experiment and simulations. The subwavelength effect is exploited for making antireflective and highly reflective waveguide facets as well as efficient fiber-chip coupling structures. We demonstrate experimentally that by etching triangular SWGs into SOI waveguide facets, the facet power reflectivity can be reduced from 31% to <2.5%. Similar structures using square gratings can also be used to achieve high facet reflectivity. Finite difference time-domain simulations show that >94% facet reflectivity can be achieved with square SWGs for 5 μ m thick SOI waveguides. Finally, SWG fiber-chip couplers for SOI photonic wire waveguides are introduced, including design, simulation, and first experimental results.